2012
DOI: 10.1111/j.1651-2227.2012.02722.x
|View full text |Cite
|
Sign up to set email alerts
|

Body size and lifestyle in an urban population entering adulthood: the ‘Grow up Gothenburg’ Study

Abstract: Within this generally healthy cohort, boys were more likely to be overweight/obese than girls, although paradoxically boys were more satisfied with their appearance. Nordic girls constitute a group with particularly high risk of reporting low body self-esteem and chronic morbidity. In the longer term, the current cross-sectional data on body size, lifestyle and health will provide important baseline information for future follow-up studies of health outcomes in later life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(52 citation statements)
references
References 27 publications
(36 reference statements)
2
50
0
Order By: Relevance
“…The latter group, in turn, was inversely related to consumption of sweets and sugary drinks. Such food consumption patterns among boys have also been observed in other studies (68,79). In contrast, among girls, breakfast consumption varied directly with consumption of lunch, dinner, fruits and vegetables, and inversely with consumption of sweets and sugary drinks.…”
Section: …With Eating Habitssupporting
confidence: 82%
See 2 more Smart Citations
“…The latter group, in turn, was inversely related to consumption of sweets and sugary drinks. Such food consumption patterns among boys have also been observed in other studies (68,79). In contrast, among girls, breakfast consumption varied directly with consumption of lunch, dinner, fruits and vegetables, and inversely with consumption of sweets and sugary drinks.…”
Section: …With Eating Habitssupporting
confidence: 82%
“…In western societies, daily consumption of breakfast, fruits and vegetables is considered to be an indicator of healthy eating habits. However, studies have shown that skipping breakfast, along with low consumption of fruits and vegetables combined with high consumption of soft drinks and sweets are common among adolescents (68,79). The eating habits of children and adolescents are of special concern since behaviours formed early in life are likely to persist into adulthood (80).…”
Section: Eating Habits In Childhood and Adolescencementioning
confidence: 99%
See 1 more Smart Citation
“…Briefly, the GrowUp 1990 cohort included 5,314 students, born around 1990; the present study used data from healthy individuals born at full term (gestational age, 37-42 wk) in Sweden, where information on longitudinal growth until adult height was available (12). Weight and height had been measured by experienced nurses at well-baby clinics and at schools in Gothenburg and surrounding municipalities.…”
Section: Study Populationmentioning
confidence: 99%
“…As an indication of representativeness of the analytic sample, corresponding values for the entire sample of Nordic origin of the GrowUp 1990 -cohort at 18 y of age (n = 4,790) were: height SDS +0.05/+0.14, weight SDS + 0.09/+0.23, and BMI SDS +0.03/+ 0.18 for girls/boys, respectively (12).…”
mentioning
confidence: 99%